Mykotoxiner och deras effekt på hästens hälsa - Pilskog, Helen (SLU/Dept. of Animal Nutrition and Management (until 231231), 2010)
Abstract Mycotoxins are secondary metabolites produced by filamentous fungi. Moulds producing mycotoxins grow on various crops that are used as horse feeds. Since the treatments of mycotoxin poisoned horses are limited it is important to prevent production of mycotoxins in feed. The major mycotoxin producing moulds in horse feeds are Fusarium spp., Penicillium spp. and Aspergillus spp. Other moulds are also of concern in horse feeds. Claviceps purpurea (ergot) have been known for centuries to cause disease in both humans and animals. The mould Rhizoctonia leguminicola which can produce the mycotoxin slaframine grow on legumes and can therefore be of concern in forages. The most important mycotoxins in horse feeds are fumonisin, trichotecenes, aflatoxin, ochratoxin A, ergot alkaloids and slaframine. Zearalenone may have an impact on horse health, but it is still not completely investigated. Horses are the species most sensitive to fumonisins and the mechanisms of intoxication in horses is therefore well studied. Horses poisoned by mycotoxins show various signs from vague such as loss of appetite or depression to acute such as convulsions and sudden death. This review gives a brief summary of the most important mycotoxins known to affect horses’ health and the most common symptoms of poisoning.